AntLeads: Monthly wintertime sea-ice lead maps for the Antarctic, April-September, 2003–2023 - Umesh Dubey; Sascha Willmes; Günther Heinemann (PANGAEA, 2025)
The AntLeads dataset provides data about lead occurrences in Antarctic sea ice during wintertime (Apr-Sep) for the 21-years period of 2003-2023. It includes monthly lead frequencies (LF), i.e. a measure for how often during a month a lead was present at a specific position in the sea ice at a spatial resolution of 1 km^2. The LF data field is accompanied by a potential absolute Integration Error (pIE), which represents a per-pixel measure of absolute uncertainty for the derived LF value, caused by data gaps due to clouds in the daily data that were used to derive monthly LF maps. The AntLeads dataset provides a basis for investigations into the complex pan-Antarctic interplay between sea ice, ocean and atmosphere. The presented data can help to better estimate and untangle the individual contribution of atmospheric and oceanic forcings on sea-ice lead dynamics in the Southern Ocean.